The Effect of Continuous Home Visits and Health Education on the Rate of Readmissions, referrals, and Health Care Costs among Discharged Patients with Heart Failure - Sh Salehitali; A Hasanpour Dehkordi; SM Hoseini Hafshejani; A Jafarei (Tehran University of Medical Sciences, 2010)
Background & Aim: Despite the advancement of medical science, readmission of the heart failure patient remains a serous problem. The aim of this study was to assess the effect of continuous care and educational intervention on the rate of readmissions, refers to physician, and health costs in patients discharged from hospital.Methods & Materials: This study was a randomized clinical trial in which 110 patients were studied. The participants were allocated in two experimental and control groups. Data were gathered using questionnaires. Home visits were carried out in the experimental group during six months. At the end of the intervention, the rate of readmissions, referrals, and health care costs were compared in the two groups. Data were analyzed using independent t-test, Fisher;aposs exact test, and Chi-square test. Results: Results indicated that the rate of readmissions (1.65±1.01 vs. 2.74±1.07, respectively), and refers to physicians (2.73±1.24 vs. 3.32±0.94, respectively) were lower in the experiment group than the control group (P<0.05) after the intervention. The average health care cost in the intervention group (2494000±172150 Rials) did not differ significantly with the control group (2736800±167360 Rials) (P>0.05). Conclusion: The results of this study indicated that the nursing interventions such as home visits are effective in lowering readmissions and refers to physicians in patients with heart failure. It seems that home visits are necessary in promoting the patients health.